Irish Defence Forces combat medical technician training: experience of a novel university medical school-based programme. Issue 2 (12th March 2020) - Loughman, Sheila; Berry, C; Hickey, P; Kerr, G M; Bury, G
Abstract : Aims: This study explores the opinions and experiences of Irish Defences Forces' (IDF) graduates from University College Dublin's Diploma in Military Medicine Care (DMMC). It aims to identify which aspects of medical education are relevant for the development of military graduates in the role of Combat Medical Technician (CMT) in future. Methods: A validated Clinical Learning Environment Score tool was adapted and incorporated into an online survey. This was sent electronically to 71 graduates. Responses were anonymous. Results: 38 (54%) graduates responded. Student feedback was positive regarding teaching and clinical placements in the DMMC. In total 16 (42%) students reported use of their new skills in their daily work. Of the 9 (24%) deployed overseas, all used their new skills. Emergency and occupational health skills were used more frequently, while advanced skills were used rarely. Conclusion: An increased emphasis on frequently used skills should be considered. Links to healthcare services would be of benefit to graduates in skills maintenance. Key advanced skills, such as intravenous cannulation and advanced airway management are rarely used but mechanisms to maintain them will improve the relevance of the programme to the CMT role. A change in how the IDF acknowledges qualifications may support more graduates in advancing and maintaining their career in the military medical workforce.